24-Hour versus daytime intraocular pressure phasing in the management of patients with treated glaucoma. Issue 8 (3rd December 2009) - Moodie, Jonathan; Wilde, Craig; Rotchford, Alan P; Vernon, Stephen A; King, Anthony J
Abstract : Aims: To determine the value of daytime and 24-h phasing in patients treated for progressive glaucoma despite apparently adequate intraocular pressure (IOP) control. Methods: A retrospective analysis of a cohort of patients that had undergone either daytime phasing (08:00–18:00) or 24-h phasing was conducted. IOP measurements were compared between those taken in clinic, daytime phasing and 24-h phasing. The frequency with which phasing results changed clinical management was also compared between daytime and 24-h phasing. Results: 76 patients fulfilling the study criteria were identified. Clinic and daytime phasing IOP were known for all 76 patients, nighttime IOP measurements were known for 41. There was no significant difference between mean IOP values measured in clinic and daytime phasing (p=0.062) or between clinic values and nighttime phasing (p=0.65). The mean daytime phasing IOP was significantly higher than the mean nighttime phasing IOP (p=0.038) (analysis of variance (ANOVA) for three groups, p=0.058). There was no significant difference between the mean peak IOP in clinic or daytime phasing (p=0.13) or between clinic and nighttime phasing (p=0.44). The mean daytime phasing IOP peak was significantly higher than the mean nighttime phasing IOP peak (p=0.015) (ANOVA for three groups, p=0.074). There was no significant difference in the frequency of a change in management that occurred as a result of phasing between the daytime and 24-h groups (p=0.65). Conclusions: 24-H phasing offers little advantage over daytime phasing in the identification of IOP fluctuations or peaks in patients progressing despite acceptable clinic IOP readings. Daytime phasing is likely to be more cost-effective than 24-h phasing.